Software engineering education in the era of conversational AI: current trends and future directions - Sengul, Cigdem; Neykova, Rumyana; Destefanis, Giuseppe (Frontiers in Artificial Intelligence, 2024)
The developments in conversational AI raised urgent questions about the future direction of many aspects of society, including computing education. The first reactions to the fast-paced evolution of conversational agents were varied: Some announced “the end of programming,” while others considered this “premature obituary of programming.” Some adopted a defensive approach to detecting the use of conversational AI and avoiding an increase in plagiarism, while others questioned, “So what if ChatGPT wrote it?” Nevertheless, questions arise about whether computing education in its current form will still be relevant and fit for purpose in the era of conversational AI. Recognizing these diverse reactions to the advent of conversational AI, this paper aims to contribute to the ongoing discourse by exploring the current state through three perspectives in a dedicated literature review: adoption of conversational AI in (1) software engineering education specifically and (2) computing education in general, and (3) a comparison with software engineering practice. Our results show a gap between software engineering practice and higher education in the pace of adoption and the areas of use and generally identify preliminary research on student experience, teaching, and learning tools for software engineering.